Estimated blood pressure trajectories and hypertension patterns among pregnant women living with HIV, Haiti, 2007–2017. Issue 3 (7th February 2022) - Tymejczyk, Olga; Deschamps, Marie Marcelle; Rouzier, Vanessa; McNairy, Margaret L.; Peck, Robert N.; Malha, Line; Macius, Youry; Fitzgerald, Daniel W.; Pape, Jean W.; Nash, Denis
Abstract: Hypertension in pregnancy is a key driver of mortality and morbidity among Haitian women. HIV infection and treatment may worsen hypertension and increase cardiovascular disease risk. The authors examined blood pressure and hypertension patterns among 1965 women (2306 pregnancies ending in live births) in a prevention of maternal‐to‐child transmission (PMTCT) program in Port‐au‐Prince, Haiti, between 2007 and 2017. Hypertension was defined as blood pressure ≥140/90 mm Hg on two consecutive visits. Latent class analysis assessed trajectories of mean arterial pressure (MAP) and multinomial ordinal logistic regression examined factors associated with higher trajectories. Between 2007–2009 and 2013–2016, hypertension at PMTCT entry increased from 1.3% to 3.8% ( p = .005), while incidence at any time during PMTCT follow‐up increased from 5.0 to 16.1 per 100 person‐years ( p < .001). Hypertension detected ≤20 weeks and > 20 weeks of gestation (possible gestational hypertension) increased from 1.1% to 3.5% ( p = .003) and from 2.3% to 6.9% ( p < .001), respectively. Five MAP trajectories ranged from low‐stable to high‐increasing. In multivariable analysis controlling for history of antiretroviral therapy, age, parity, and weight, program entry in more recent years was associated with greater odds of higher MAP trajectory (adjusted odds ratio for 2013–2016 vs. 2007–2009 = 3.1, 95% confidence interval: 1.7–5.6). The increasing prevalence and incidence of hypertension highlight a need for screening and management prior to PMTCT entry and during follow‐up. In a population with limited access to chronic disease care, and where many deliveries occur outside of a clinical setting, the period of PMTCT follow‐up represents an opportunity to diagnose and initiate management of preexisting and pregnancy‐related hypertension.